2017
DOI: 10.3390/ijerph14070736
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Bone Health in Malaysian Middle-Aged and Elderly Women Assessed via Quantitative Ultrasound

Abstract: Risk factors for osteoporosis may vary according to different populations. We aimed to investigate the relationship between risk factors of osteoporosis and bone health indices determined via calcaneal quantitative ultrasound (QUS) in a group of Malaysian women aged 50 years or above. A cross-sectional study was performed on 344 Malaysian women recruited from a tertiary medical centre in Kuala Lumpur, Malaysia. They answered a self-administered questionnaire on their social-demographic details, medical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Meanwhile, a meta-analysis included 60,000 subjects with over 250,000 person-years reported that the risk of hip fractures with a BMI of 20 kg/m 2 was increased twofold comparing with a BMI of 25 kg/m 2 [16]. Although it was widely accepted obesity was protective against the risk of osteoporosis, newer studies suggested increasing adiposity might be harmful to bone microarchitecture [13,15,27,28]. A study conducted by Chin et al discovered BFP was inversely associated with bone health although BMI was positively associated with bone status [27].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Meanwhile, a meta-analysis included 60,000 subjects with over 250,000 person-years reported that the risk of hip fractures with a BMI of 20 kg/m 2 was increased twofold comparing with a BMI of 25 kg/m 2 [16]. Although it was widely accepted obesity was protective against the risk of osteoporosis, newer studies suggested increasing adiposity might be harmful to bone microarchitecture [13,15,27,28]. A study conducted by Chin et al discovered BFP was inversely associated with bone health although BMI was positively associated with bone status [27].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, to the best of our knowledge, this is the first study to report on the prevalence and predictors of osteoporosis defined by DXA among middle-aged and elderly Malaysian Chinese in Klang Valley. Other similar studies have been conducted in Malaysia, but they used quantitative ultrasonometry to determine bone health of the subjects [13,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…For beverages, an intake of less than one unit per week was defined as non-drinker. One unit of milk was defined as 200 mL, while one unit of coffee/tea was defined as one standard cup [13]. Those who consumed beverages or dairy products 3-4 days per week were defined as regular drinkers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a meta-analysis included 60000 subjects with over 250000 person-years reported that the risk of hip fracture with a BMI of 20 kg/m 2 was increased two-fold comparing with a BMI of 25 kg/m 2 [16]. Although it was widely accepted obesity was protective against the risk of osteoporosis, newer studies suggested increasing adiposity might be harmful to bone microarchitecture [13,15,27,28]. A study conducted by Chin et al discovered BFP was inversely associated with bone health although BMI was positively associated with bone status [27].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%